DEVELOPMENT OF THE PENTAHELIX TO HEXAHELIX MODEL IN RAJAPOLAH TASIKMALAYA HANDICRAFT SMEs - Depy Muhamad Pauzy; Ristina Siti Sundari; Hary Firmansyah (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
This study aims to develop the pentahelix model into a hexahelix model to strengthen woven handicraft Small and Medium Enterprises (SMEs) in Rajapolah, Tasikmalaya. The traditional pentahelix model, involving government, academia, business actors, communities, and media, has not fully addressed challenges related to financing access, innovation sustainability, and SME performance. Therefore, this study introduces financial institutions as a sixth actor within a collaborative hexahelix framework. Data were analyzed using NVivo 12 Pro based on in-depth interviews with relevant stakeholders. The findings reveal that financial institutions have not yet become an effective driver of business expansion due to entrepreneurs’ concerns regarding interest payments, financing requirements, and installment obligations. Many SME owners remain reluctant to utilize formal financing because of uncertainty about their ability to meet future repayment commitments amid changing business conditions. Nevertheless, the hexahelix model has the potential to foster stronger cross-sector collaboration and support the sustainability of culture-based local economies, provided that entrepreneurs’ financial literacy improves and financial institutions offer more accessible and secure financing schemes.